“almost invisible until now”: Antigone, Ismene, and the Dramaturgy of Tragedy - Hagström-Ståhl, Kristina (Nordic Theatre Studies, 2019)
This essay discusses Sophocles’ Antigone in relation to its Hegelian legacy, engaging with the play from a directorial perspective. Drawing on the work of Judith Butler, Anne Carson , Bonnie Honig, Peggy Phelan and Cecilia Sjöholm, I attempt to envision a contemporary mise en scène that repositions feminine subjectivity within the dramaturgy of tragedy. Centering on the relationship between Antigone and Ismene, as well as on the possibility of revaluing Ismene’s position in terms of political and dramaturgical agency, I hope to challenge dramaturgical conventions that assume binary, heteronormative relations as the primary framework of interpretation for female characters, and death and destruction as the only possible outcome for what is positioned as feminine. This resituated reading of the drama examines the function of embodied performance in processes of meaning-making, and offers dramaturgical structure as a site for strategies of resistance.